Versatile Implementation in Angle-Resolved Optical Microscopy: Its Application to Local Spectrometry of Microcavities with PIC-J-Aggregates. (28th February 2011) - Obara, Yuki; Saitoh, Keita; Oda, Masaru; Tani, Toshiro
Abstract : Versatile novel implementations in microspectroscopy are developed, which can provide angle-resolved optical spectroscopy at local sample areas almost in diffraction limit. By selecting focus position of light flux incident within the back focal plane of the objective lens radially from the position of the optical axis of the microscope with employing off-centered pinhole, we can obtain parallel beam with oblique incidence and its angle tuning at the sample surface. In this paper, we describe our specific optical setup and its practical working principle in detail. We report, as a demonstration of its performance, our latest studies on optical properties of cavity polariton states in the so-called quantum microcavity structures, which contain molecular J-aggregates of pseudoisocyanine (PIC) dye as active working materials. By using the microscope technique, we obtain a fair amount of improvement in the linewidth observation of cavity polariton spectra.